Analysis of Corn Drying Rack Position on Tray Type Dryer on Drying Rate - Sutanto, Rudy; Tira, Hendry Sakke (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research aims to determine the drying characteristics of corn kernels using a tray-type dryer, including the moisture content of the corn kernels over time, the mass of the tested corn kernels over time and the drying rate over time. This research uses the experimental method. The drying process uses an incoming drying hot air temperature of 65ºC with an incoming hot drying air speed of 2 m/s, repeated three times until a water content of 14 ± 0.5% is reached. The dryer in this study used four stacking shelves counting from the bottom, which were filled with 500 grams per shelf. This research shows that the further the shelf is positioned from the incoming hot drying air, the lower the drying rate. Vice versa, the closer the drying Shelf is to the incoming hot air, the greater the drying rate. The average decrease in corn kernel mass was 0.95% for shelf 1, 0.93% for shelf 2, 0.90% for shelf 3 and 0.88% for shelf 4 during a drying period of 3.5 hours. The average decrease in water content was 4.4% for shelf 1, 4.29% for shelf 2, 4.15% for shelf 3 and 4% for shelf 4 during a drying period of 3.5 hours. The further the position of the shelf from the hot air dryer, the less air content contained in the material on the shelf can be absorbed by the hot air dryer and vice versa. The average drying rate was 16.8% for shelf 1, 15% for shelf 2, 13.6% for shelf 3 and 12.8% for shelf 4 during a drying period of 3.5 hours at a drying hot air temperature of 65oC with a drying air speed of 2 m/s. The research data analysis results showed that the hot air dryer should not be passed from below but rather from the side. This affects the drying process in the dryer and makes it evener.